2021
DOI: 10.1038/s41591-021-01535-y
|View full text |Cite
|
Sign up to set email alerts
|

The lesson of ivermectin: meta-analyses based on summary data alone are inherently unreliable

Abstract: The lesson of ivermectin: meta-analyses based on summary data alone are inherently unreliable To the Editor -The global demand for prophylactic and treatment options for COVID-19 has in turn created a demand for both randomized clinical trials, and the synthesis of those trials into meta-analyses by systematic review. This process has been

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
63
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(68 citation statements)
references
References 5 publications
0
63
0
Order By: Relevance
“…In this light, there is also no problem in analyzing one and the same data set in different ways to explore the sensitivity of results to violations of assumptions (Greenland 2020) -as long as these explorations are fully reported, not just the ones producing a desired outcome such as the smallest P-value. And perhaps even more important than full reporting of summary statistics is that we ensure free access to the underlying raw data for meta-analysts (Lawrence et al, 2021;Whitlock et al, 2010).…”
Section: Full Reporting Rather Than Filtering Of Resultsmentioning
confidence: 99%
“…In this light, there is also no problem in analyzing one and the same data set in different ways to explore the sensitivity of results to violations of assumptions (Greenland 2020) -as long as these explorations are fully reported, not just the ones producing a desired outcome such as the smallest P-value. And perhaps even more important than full reporting of summary statistics is that we ensure free access to the underlying raw data for meta-analysts (Lawrence et al, 2021;Whitlock et al, 2010).…”
Section: Full Reporting Rather Than Filtering Of Resultsmentioning
confidence: 99%
“…Worse again, poor research practices can even fuel misinformation [ 45 , 46 ] (and disinformation) around science and medicine, giving a veneer of respectability to wrong-headed positions. Pertinent examples of this range from the fraudulent research that deviously and wrongly linked the measles-mumps-rubella vaccine to autism [ 47 , 48 ], to the substandard trials that gave the false impression ivermectin was a viable COVID treatment [ 49 , 50 ]. The unsettling reality is that poor statistical practice renders swathes of biomedical research worse than useless.…”
Section: Discussionmentioning
confidence: 99%
“…Recent meta-analyses have shown that ivermectin is not beneficial for the prevention or treatment of COVID-19 1 . In addition, the largest clinical trial showing a benefit of ivermectin was recently withdrawn by the preprint organization that had posted it, due to discrepancies identified in individual patient data 2,3 .…”
Section: Promotion Of Non-evidence-based Therapeutics Within Patient-led Long Covid Support Groupsmentioning
confidence: 99%
“…Unfortunately, the use of ivermectin has been widely promoted based on flawed data and without regard for the analyses of subsequent studies 3 . This is similar to the situation with hydroxychloroquine in 2020, in which the use of the drug was widely promoted based on a limited number of small-scale studies showing a potential benefit in acute COVID-19 disease.…”
Section: Promotion Of Non-evidence-based Therapeutics Within Patient-led Long Covid Support Groupsmentioning
confidence: 99%
See 1 more Smart Citation